The Effect of Product Quality, Product Innovation, Capital and Marketing Strategy on the Development of MSMEs in Simalungun Regency Trade - Sirait, Ririn Eka Sasnita; Siahaan, Anggiat Maruli; Sitorus, Paskah Ria; Gultom, Lamtiur Lidia (International Journal of Economics Development Research (IJEDR), 2025)
This research investigates the influence of product quality, product innovation, capital, and marketing strategy on the development of micro, small, and medium enterprises (MSMEs) in trade districts. The study aims to determine whether these factors significantly contribute to MSME development. The population and sample were selected using purposive sampling. Data were collected through questionnaires and analyzed using SPSS software. The results of simple regression analysis show that product quality, capital, and marketing strategy have a significant influence on the development of MSMEs. However, product innovation does not have a significant influence on MSME development.